Smokeless tobacco use in Sweden and other 17 European countries - Leon, Maria E; Lugo, Alessandra; Boffetta, Paolo; Gilmore, Anna; Ross, Hana; Schüz, Joachim; La Vecchia, Carlo; Gallus, Silvano (European journal of public health, 2016)
INTRODUCTION: The purpose of this study is to report prevalence and determinants of use of smokeless tobacco in a representative sample of men and women from Sweden, where Swedish snus sales are legal, and from 17 other European countries, where sales of smokeless tobacco are restricted. METHODS: In 2010, a face-to-face survey including information on current smokeless tobacco use was conducted in a representative sample of around 1000 individuals aged ≥15 years per country in Albania, Austria, Bulgaria, Czech Republic, Croatia, England, Finland, France, Greece, Hungary, Ireland, Italy, Latvia, Poland, Portugal, Romania, Spain and Sweden. RESULTS: In Sweden, the overall prevalence of smokeless tobacco use was 12.3% (20.7% in men, 3.5% in women). The corresponding estimate for other European countries combined was 1.1% (1.2% in men, 1.1% in women). Compared with never smokers, former smokers in Sweden were significantly more likely to use smokeless tobacco (odds ratio, OR: 2.67), whereas no difference in use was observed in other countries (OR: 1.04). Use of smokeless tobacco was similar among current smokers in Sweden (OR: 1.96) and in other countries (OR: 2.40) when contrasted to never smokers. In Sweden there were no differences in the number of cigarettes/day between smokers who also use smokeless tobacco (13.3 cigarettes/day) and exclusive cigarette smokers (12.9 cigarettes/day; P = 0.785). CONCLUSIONS: Excluding Sweden, current oral tobacco use was not commonly reported in the European countries surveyed and was similarly rare both in men and in women. In Sweden, however, use of smokeless tobacco was about 10-fold higher than the rest of Europe and more prevalent in men than in women.
Keywords: dospělí; Rumunsko; Romania; Švédsko; Bulharsko; Smoking; Female; Europe; Ireland; bezdýmný tabák; Prevalence; Adult; Portugal; mladý dospělý; ženské pohlaví; Greece; Adolescent; kouření; Finland; Albánie; lidé; Finsko; Evropa; Austria; Francie; Aged, 80 and over; užívání tabáku; Tobacco, Smokeless; Humans; prevalence; Irsko; Male; Sweden; Aged; Bulgaria; Croatia; Czech Republic; Chorvatsko; Young Adult; France; Hungary; Česká republika; Albania; Tobacco Use; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Maďarsko; Poland; Portugalsko; Middle Aged; mladiství; Řecko; Rakousko; Polsko